Preventive Cancer Stem Cell‐Based Vaccination Reduces Liver Metastasis Development in a Rat Colon Carcinoma Syngeneic Model123. (25th February 2013) - Duarte, Sonia; Momier, David; Baqué, Patrick; Casanova, Vincent; Loubat, Agnès; Samson, Michel; Guigonis, Jean‐Marie; Staccini, Pascal; Saint‐Paul, Marie‐Christine; De Lima, Maria Pedroso; Carle, Georges F.; Pierrefite‐Carle, Valérie
Abstract Cancer stem cells (CSCs) represent a minor population of self‐renewing cancer cells that fuel tumor growth. As CSCs are generally spared by conventional treatments, this population is likely to be responsible for relapses that are observed in most cancers. In this work, we analyzed the preventive efficiency of a CSC‐based vaccine on the development of liver metastasis from colon cancer in a syngeneic rat model. We isolated a CSC‐enriched population from the rat PROb colon carcinoma cell line on the basis of the expression of the aldehyde dehydrogenase‐1 (ALDH1) marker. Comparative analysis of vaccines containing lysates of PROb or ALDHhigh cells by mass spectrometry identifies four proteins specifically expressed in the CSC subpopulation. The expression of two of them (heat shock protein 27‐kDa and aldose reductase) is already known to be associated with treatment resistance and poor prognosis in colon cancer. Preventive intraperitoneal administration of vaccines was then performed before the intrahepatic injection of PROb cancer cells. While no significant difference in tumor occurrence was observed between control and PROb‐vaccinated groups, 50% of the CSC‐based vaccinated animals became resistant to tumor development. In addition, CSC‐based vaccination induced a 99.5% reduction in tumor volume compared to the control group. To our knowledge, this study constitutes the first work analyzing the potential of a CSC‐based vaccination to prevent liver metastasis development. Our data demonstrate that a CSC‐based vaccine reduces efficiently both tumor volume and occurrence in a rat colon carcinoma syngeneic model. STEM CELLS2013;31:423–432